Character Associations and Path Coefficient Analysis for Grain Yield and Yield Contributing Traits in Pearl Millet [Pennisetum glaucum (L.) R. Br.]: Character Associations and Path Coefficient Analysis in Pearl Millet - Jain, S K; Deewan, Dinesh Kumar Deewan; Om Prakash; L D Sharma (Annals of Arid Zone, 2023)
The present investigation was conducted on forty genotypes of pearl-millet to estimate the nature and magnitude of genetic variability, correlation and path analysis for different yield and their contributing traits. The analysis of variance revealed significant variability among genotypes for all the traits studied. The phenotypic coefficient of variation (PCV) was more significant than genotypic coefficient of variation (GCV), which reflected the influence of environmental factors on the traits. High PCV and GCV were observed for plant height followed by 1000-grain weight and grain yield per plant. Due to the additive gene effects, the plant height showed the highest heritability coupled with high genetic advance as a percent of the mean. While other yield traits like panicle diameter, effective tiller per plant, 1000-grain weight, grain yield per plant, days to maturity and panicle length have moderate value of heritability and genetic gain. The association analysis revealed that grain yield per plant had significant positive correlations with plant height, 1000 grain weight, biological yield per plant and harvest index both at genotypic and phenotypic levels. Path analysis revealed that the biological yield per plant, 1000-grain weight, harvest index, plant height and days to maturity showed higher compensation due to uprising positive direct effect and positive correlation with grain yield per plant. Hence, the present study emphasizes these traits in future crop improvement programme in pearl millet.